Structural basis of complex formation between mitochondrial anion channel VDAC1 and Hexokinase-II - Nandan Haloi (Nature Portfolio, 2021)
Haloi et al. investigate the role of the hydrophobic N-terminus of hexokinase II (HKII) in their binding to mitochondrial VDAC1. They use a hybrid approach combining molecular and Brownian dynamics to show that HKII first inserts into the outer membrane of mitochondria (OMM) and then interacts with VDAC1 on the cytosolic surface of OMM to form a binary complex.